The Role of Curcumin to PGF2a and the Primary Dysmenorrhea Pain Intensity - Amalia, Rizki; Qadar, Sriwijaya; UP, Nugraha; Abdullah, Nusratuddin; Sunarno, Isharyah; Kasim, Firdaus (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to rate the effectiveness of giving curcumin 7 days before menstruation in order to decrease the pain intensity of women with primary dysmenorrhea. The research is using randomized controlled trial method analysis with block permutation on women with primary dysmenorrhea. The statistical data was then processed using SPSS 21. The level of PGF2a in women that consume curcumin decreased significantly from 677.31 ± 387.27 to 419 ± 234.58 with the ratio P 0.001 compared to the control group. The average scale of the visual analog scale (VAS) also decreased significantly for women that were given curcumin supplementation, which was from 5.33 ± 1.56 to 2.67 ± 1.15 with the ratio P 0.000. The research has shown that supplementation of curcumin has certain role in decreasing the pain intensity and the prostaglandin F2A content in women with primary dysmenorrhea.